FAKTOR-FAKTOR YANG MEMPENGARUHI PERSISTENSI LABA PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - Farihatul Ula Riskiya; Laely Aghe Africa (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2022)
Investors keep investing in the company with the aim of seeing how far the company's ability to generate profits. The company is said to be good if able to achieve the desired profit target. Profit is an indicator of the company in attracting investors to invest. This research aims to prove empirically about the effect of accrual reliability, cash flow operations, sales volatility, and firm size on earnings persistence. This research was conducted at manufacturing companies in the goods industry sector consumption listed on the Indonesia Stock Exchange in 2015-2018. Method determination of the sample in this study using purposive sampling criteria for manufacturing companies using the currency Rp not experiencing a loss, the company is consistently listed that listed on the Indonesia Stock Exchange for the period 2015-2018 in order to obtain a sample as many as 112 companies. The analysis technique used in this study namely multiple linear regression analysis. Based on the research results, it is known that the reliability of accruals and operating cash flows has a positive effect on earnings persistence. Sales volatility and firm size have no effect on earnings persistence.